Optimization of drug combinations using Feedback System Control - Nowak-Sliwinska, Patrycja; Weiss, Andrea; Ding, Xianting; Dyson, Paul J; van den Bergh, Hubert; Griffioen, Arjan W; Ho, Chih-Ming (Nature protocols, 2016)
Nowak-Sliwinska et al . describe a protocol for optimizing drug combinations using Feedback System Control (FSC). Drug combinations are tested in a cell-based assay in which results are entered into the FSC pipeline to predict new combinations to be tested in vitro . We describe a protocol for the discovery of synergistic drug combinations for the treatment of disease. Synergistic drug combinations lead to the use of drugs at lower doses, which reduces side effects and can potentially lead to reduced drug resistance, while being clinically more effective than the individual drugs. To cope with the extremely large search space for these combinations, we developed an efficient combinatorial drug screening method called the Feedback System Control (FSC) technique. Starting with a broad selection of drugs, the method follows an iterative approach of experimental testing in a relevant bioassay and analysis of the results by FSC. First, the protocol uses a cell viability assay to generate broad dose-response curves to assess the efficacy of individual compounds. These curves are then used to guide the dosage input of each drug to be tested in combination. Data from applied drug combinations are input into the differential evolution (DE) algorithm, which predicts new combinations to be tested in vitro . This process identifies optimal drug-dose combinations, while saving orders of magnitude in experimental effort. The complete optimization process is estimated to take ∼4 weeks. FSC does not require insight into the disease mechanism, and it has therefore been applied to find combination therapies for many different pathologies, including cancer and infectious diseases, and it has also been used in organ transplantation.